2017
DOI: 10.17586/2220-8054-2017-8-4-535-539
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions in nanostructured K1-x(NH4)(x)H2PO4 (x = 0 – 0.15) solid solutions

Abstract: Effect of ammonium dihydrogen phosphate admixture on phase transitions in nanostructured solid solutions (1 − x)KH 2 PO 4 -(x)(NH 4 )H 2 PO 4 at x = 0, 0.05 and 0.15 has been studied by dielectric spectroscopy. The samples have been prepared by embedding of aqueous solutions into porous borosilicate glasses. The X-ray diffraction have shown that the crystal structure at room temperature corresponds to the bulk KDP and the average nanoparticle diameters are 49 (2) nm for the sample with 5 % of (NH 4 )H 2 PO 4 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
1
4
0
1
Order By: Relevance
“…The principle feature of all dependences C(T ) is the presence of a shift in the maximum position on cooling and heating. We have observed a similar hysteresis for NCM based on conventional PG [6] with embedded KADP. Temperatures of ferroelectric phase transition (T C ) on cooling and heating have been determined from the maximum positions for every sample, with an accuracy in the determination of T C of better than 0.1 K. In Fig.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…The principle feature of all dependences C(T ) is the presence of a shift in the maximum position on cooling and heating. We have observed a similar hysteresis for NCM based on conventional PG [6] with embedded KADP. Temperatures of ferroelectric phase transition (T C ) on cooling and heating have been determined from the maximum positions for every sample, with an accuracy in the determination of T C of better than 0.1 K. In Fig.…”
Section: Resultssupporting
confidence: 67%
“…The phase diagram for the bulk KH 2 PO 4 (KDP) and (NH 4 )H 2 PO 4 (ADP) solid solutions (KADP) are known [4,5] and it is shown that a small admixture of ADP leads to a drastic decreasing of the ferroelectric phase transition temperature T C . In previous work [6] we studied the effect of restricted geometry on this phase transition for NCM based on conventional porous glasses (PG) with KADP at low ADP concentrations. It has been revealed that there are the shifts in the ferroelectric phase transition temperature, to higher temperature T C , as a function of ADP concentration on cooling and heating in comparison with the bulk KADP at the same (NH 4 )H 2 PO 4 concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An influence of the pore size on the phase transition temperature in KDP and ADP particles, embedded in porous matrices, has already been discussed [8][9][10][11]13]. However, experimental results obtained by different authors contain some contradictions.…”
Section: Discussionmentioning
confidence: 99%
“…Alongside this, potassium dihydrogen phosphate [8][9][10][11][12][13], Rochelle salt [14,15], and triglycine sulfate [14,[16][17][18][19], in contrast, are characterized by an increase of ferroelectric phase transition temperature under "restricted geometry" conditions. However the data on the magnitude of T C shifting as a function of the matrix mean that the pore diameter varied significantly for different researchers.…”
Section: Introductionmentioning
confidence: 99%